Correlation between nicotine dependence and inflammatory biomarkers in Thai smokers: eight weeks of synbiotic intervention - Ekasit Lalitsuradej; Parama Pratummas; Phakkharawat Sittiprapaporn; Chaiyavat Chaiyasut (Institute of Advanced Engineering and Science, 2022)
Cigarette smoke contains thousands of man-made substances, and many may contribute to addiction and inflammation. This study examined the effect of synbiotics on the Fagerstrom test for nicotine dependence (FTND) and inflammatory markers in Thai smokers. 14 smokers with a Nicotine Dependence Fagerstrom Test scores of 4 or higher and no pregnancy or lactation history participated in this study. We gave them surveys about the FTND and continued blood tests for Lipopolysaccharide (LPS), lactulose and mannitol ratios (LMR), Quinolinic acid (QA), and 5-hydroindoleacetic acid (5-HIAA) to record inflammatory marker levels and leaky gut information. Pearson's R-values for LPS and LMR were 0.444 and -0.465. FTND showed a positive correlation with LPS and a negative correlation with leaky gut, but both relationships were weak due to no correlation for LPS but leaky gut. The R2 of the LPS correlation coefficient was 0.197, p = 0.112, and the R2 of the leaky gut correlation was 0.217, p 0.001. FTND, LMR, and QA were significantly reduced, while 5-HIAA was elevated. Further investigation is needed to determine the association between smoking and inflammation. In conclusion, synbiotics improved FTND, gut permeability, and inflammation.